ANALISIS PERKEMBANGAN TINGKAT LITERASI KEUANGAN PENGGUNA FINTECH PADA PELAKU USAHA MIKRO DI KABUPATEN SUMENEP (STUDI KASUS USAHA MIKRO PENGGUNA FINTECH PAYMENT SHOPEEPAY DAN OVO) - Yusi Yuliarisa; Aprilya Dwi Yandari (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2022)
Fintech Payment is Technology Payment Systemwho has a purpose to incrase,simplify,and offer in a new wayto wile Micro Business Actorthat can incrase Financial Literacy. The purpose of this Research is to analyze Level of Financial Literacy of Fintech Payment User for Micro Busniness Actor in Sumenep Regency. Kind of this researchs are use qualitative method ,by using interview .Technique of determining the sources are using accidental sampling. The knowledge of micro busisess actors in Sumenep Regency regarding Fintech Payments is still fairly limited because the informants only know Fintech Payments only as payments. Micro-enterprises in Sumenep Regency do not fully understand the use of Fintech Payment, this is because digital literacy is still lacking. Micro-enterprises in Sumenep Regency have sufficient skills because they can explain the cost incurred and in using the features in it, one of which is to record sales properly so that bussines actors to manage transactions. Good financial reports. Micro business actors also believe in ensuring that the data sent is also safe. All resource persons have sufficient literate financial literacy because they have a general set of knowledge about Fintech Payment, confidence and skills in using Fintech Payment